Knockdown of lncRNA ENST00000603829 Inhibits the Proliferation and Invasion of Salivary Gland Pleomorphic Adenoma through Regulating Cyclin D1 - Yi Xu; Xin Sun; Jing Chen; Jinbiao Xu; Junshui Wei (Applied Bionics and Biomechanics)
Objective. Salivary gland pleomorphic adenoma (SPA) is a benign neoplasm that can still recur even after radical surgery. To investigate its underlying pathogenesis, here, we examined the significance of lncRNA ENST00000603829 in the proliferation and invasion of SPA. Methods. SPA tissues (n=30) and adjacent normal tissues (NC; n=30) were collected from SPA patients treated at our hospital from June 2017 to December 2019. The human normal salivary gland epithelial cell line (HSG) and SPA cells (PA30, PA37, and PA116) were cultured. qRT-PCR was used for detecting the expression of cyclin D1 and lncRNA ENST00000603829 in tissues and cells. lncRNA ENST00000603829/cyclin D1 was knocked down or overexpressed in PA116 cells. The expression of cyclin D1 and lncRNA ENST00000603829 in different cell lines was examined using qRT-PCR. Transwell assays and cell counting kit-8 (CCK-8) were used to assess cellular invasion and proliferation. The testing result regarding the apoptosis rate and cell cycle was obtained via flow cytometry. Western blot provided the measurement of cyclin D1 expression in cells. Results. We observed an upregulation of lncRNA ENST00000603829 and cyclin D1 expression in SPA tissues and cells. Knockdown of lncRNA ENST00000603829 inhibited cell invasion and proliferation, promoting apoptosis and retaining the cells during the G0/G1 phase. However, such effects of lncRNA ENST00000603829 knockdown were inhibited when cyclin D1 was overexpressed. Conclusion. lncRNA ENST00000603829 can promote the occurrence and development of SPA through increasing cyclin D1 expression.